Morphology-tuned Pt3Ge accelerates water dissociation to industrial-standard hydrogen production over a wide pH range - Mondal, Soumi; Sarkar, Shreya; Bagchi, Debabrata; Das, Tisita; Das, Risov; Singh, Ashutosh Kumar; Prasanna, Ponnappa Kechanda; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (Advanced Materials, 2022)
The discovery of novel materials for industrial-standard hydrogen production is the present need considering the global energy infrastructure. A novel electrocatalyst, Pt3Ge, which is engineered with a desired crystallographic facet (202), accelerates hydrogen production by water electrolysis, and records industrially desired operational stability compared to the commercial catalyst platinum is introduced. Pt3Ge-(202) exhibits low overpotential of 21.7 mV (24.6 mV for Pt/C) and 92 mV for 10 and 200 mA cm(-2) current density, respectively in 0.5 m H2SO4. It also exhibits remarkable stability of 15 000 accelerated degradation tests cycles (5000 for Pt/C) and exceptional durability of 500 h (@10 mA cm(-2)) in acidic media. Pt3Ge-(202) also displays low overpotential of 96 mV for 10 mA cm(-2) current density in the alkaline medium, rationalizing its hydrogen production ability over a wide pH range required commercial operations. Long-term durability (>75 h in alkaline media) with the industrial level current density (>500 mA cm(-2)) has been demonstrated by utilizing the electrochemical flow reactor. The driving force behind this stupendous performance of Pt3Ge-(202) has been envisaged by mapping the reaction mechanism, active sites, and charge-transfer kinetics via controlled electrochemical experiments, ex situ X-ray photoelectron spectroscopy, in situ infrared spectroscopy, and in situ X-ray absorption spectroscopy further corroborated by first principles calculations.
Keywords: Electrochemistry; hydrogen production; intermetallics; water electrolysis